2016
DOI: 10.1007/s13197-016-2332-7
|View full text |Cite
|
Sign up to set email alerts
|

Production and storage stability of formulated chicken nuggets using konjac flour and shiitake mushrooms

Abstract: Formulated chicken nuggets which are low in fat and, high in dietary fiber and free from phosphate were developed by adding various levels of a konjac flour/xanthan gum (KF/XG) (3:1) mixture (0.2-1.5 %, w/w) and shiitake powder (SP) (1-4 %, w/w). A central composite rotatable design was used to investigate the influence of variables on the physical and sensory properties of nuggets and to optimize the formulated nugget formulation. The addition of the KF/XG mixture and SP was effective in improving nugget firm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 30 publications
2
37
0
4
Order By: Relevance
“…Recently, Adebayo et al () reported an inhibitory effect of Pleurotus species against gram‐positive and gram‐negative, but the inhibitory effect varied according to the mushroom species and strain. In our study, the mixed microbial flora contributed to the mild diminution of the pH values since the lactic acid produced by the LAB was partially neutralized via the action of endogenous and spoilage bacteria enzymes on the meat protein (Akesowan, ; Bao et al, ). This proteolytic activity led to an upturn in the pH of CMF and CLF at 13 days of storage, associated with the increased counts of Pseudomonas in these samples.…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…Recently, Adebayo et al () reported an inhibitory effect of Pleurotus species against gram‐positive and gram‐negative, but the inhibitory effect varied according to the mushroom species and strain. In our study, the mixed microbial flora contributed to the mild diminution of the pH values since the lactic acid produced by the LAB was partially neutralized via the action of endogenous and spoilage bacteria enzymes on the meat protein (Akesowan, ; Bao et al, ). This proteolytic activity led to an upturn in the pH of CMF and CLF at 13 days of storage, associated with the increased counts of Pseudomonas in these samples.…”
Section: Resultsmentioning
confidence: 81%
“…Nevertheless, these parameters were similar between the products with the replacement of fat by mushroom flours and the control with 10% fat. In general, when meat products are incorporated with some items, like seaweed (Cox & Abu‐Ghannam, ; López‐Lopez et al, ), oat‐derived soluble fiber (Piñero et al, ), lemon albedo (Aleson‐Carbonell et al, ), vegetal and algae proteins (Parniakov et al, ) and shiitake powder (Akesowan, ) softer products are formed when compared with the original counterparts. The hardness reduction has been explained by the superior fat and water retention abilities of nonmeat ingredients relative to meat ingredients (Aleson‐Carbonell et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations